Characterization of Esophageal Microbiota in Patients With Esophagitis and Esophageal Squamous Cell Carcinoma - Zongdan Jiang (Frontiers Media S.A., 2021)
Microbial imbalances have been well elucidated in esophageal adenocarcinoma. However, few studies address the microbiota in esophageal squamous cell carcinoma (ESCC) and esophagitis (ES). We aimed to explore the association of esophageal microbiota with these patients. Esophageal tissues were obtained from healthy controls and ES and ESCC patients undergoing upper endoscopy. 16S rRNA gene sequencing was applied to analyze the microbiome. The α and β diversity differences were tested by Tukey test and partial least squares-discriminant analysis (PLS-DA), respectively. Linear discriminant analysis effect size (LEfSe) analysis was performed to assess taxonomic differences between groups. A total of 68 individuals were enrolled (control = 21, ES = 15, ESCC = 32). Microbial diversity was significantly different between the ESCC patients and healthy controls by Chao1 index, Shannon index, and PLS-DA. Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, and Fusobacteria were the five dominant bacterial phyla among the three groups. Megamonas, Collinsella, Roseburia, and Ruminococcus_2 showed a significantly continuous decreasing trend from the control group to the ESCC group at the genus level. When compared with the control group, decreased Fusobacteria at phylum level and Faecalibacterium, Bacteroides, Curvibacter, and Blautia at genus level were detected. ESCC samples also displayed a striking reduction of Bacteroidetes, Faecalibacterium, Bacteroides, and Blautia in comparison with the ES patients. LEfSe analysis indicated a greater abundance of Streptococcus, Actinobacillus, Peptostreptococcus, Fusobacterium, and Prevotella in the ESCC group. Our study suggests a potential association between esophageal microbiome dysbiosis and ESCC and provides insights into potential screening markers for esophageal cancer.